Assessing soil erosion risk in Kazakhstan: A RUSLE-based approach for land rehabilitation - Kaliyeva, Damira; Tokbergenova, Aigul; Mirzabaev, Alisher; Zulpykharov, Kanat; Bissenbayeva, Sanim; Taukebayev, Omirzhan; Qadir, Manzoor (HARD Publishing Company, 2025)
Soil degradation is increasing in Kazakhstan, leading to severe losses in land productivity. The Almaty region, the country’s leading agricultural and industrial province, is among the most affected areas. The objective of this study is to evaluate, for the first time, the applicability of the revised model of the Universal Soil Loss Equation (USLE) for estimating the rate of soil erosion and identifying areas susceptible to soil erosion in the Almaty region. The revised USLE (RUSLE) factors, including rainfall erosivity, soil erodibility, slope length, and steepness, were represented using data on soil, topography, and land use/vegetation cover from the region. Using the RUSLE model’s algorithms, we generated an erosion risk map, emphasizing areas with a high potential for erosion. The results show higher soil erosion rates in agricultural areas with steep slopes and inadequate environmental practices – annual soil losses in the region are as high as 26,279 t/ha/year in high-risk areas. On average, approximately 88% of the region’s territory loses up to 103 t/ha/year, while 9% loses about three times as much. Such potential soil erosion risks warrant the implementation of efficient soil conservation strategies in the region to protect soils, ensure desired agricultural productivity, and support the journey in achieving the Sustainable Development Goal (SDG) 15.